Metabolic Reprogramming During Multidrug Resistance in Leukemias - Vidal, Raphael Silveira; Quarti, Julia; Rodrigues, Mariana Figueiredo; Rumjanek, Franklin D.; Rumjanek, Vivian M. (Frontiers in Oncology, 2018)
Cancer outcome has improved since introduction of target therapy. However, treatment success is still impaired by the same drug resistance mechanism of classical chemotherapy, known as multidrug resistance (MDR) phenotype. This phenotype promotes resistance to drugs with different structures and mechanism of action. Recent reports have shown that resistance acquisition is coupled to metabolic reprogramming. High gene expression, increase of active transport, and conservation of redox status are one of the few examples that increase energy and substrate demands. It is not clear if the role of this metabolic shift in the MDR phenotype is related to its maintenance or to its induction. Apart from the nature of this relation, the metabolism may represent a new target to avoid or to block the mechanism that has been impairing treatment success. In this mini-review we discuss the relation between metabolism and MDR resistance focusing on the multiple non metabolic functions that enzymes of the glycolytic pathway are known to display, with emphasis with the diverse activities of glyceraldehyde-3-phosphate dehydrogenase (GAPDH).